2021
DOI: 10.9734/ajaees/2021/v39i530573
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Development of Rural Women through Value Added Dairy Products

Abstract: The most important trend of development in agriculture is increasing diversification of rural economy. Contribution of agriculture sector to total GDP of state is 26 Percent. Whereas livestock sector is contributing around 38 percent of Agriculture GDP (at current prices). Today dairy enterprise is practiced by 70 million rural households in India. Milk products generate cash income to farmers almost on daily basis, unlike other crops. Clean milk production by adopting the appropriate practices is urgent need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study by Gupta et al, 2019 found that 60% of women agripreneurs in Rajasthan were engaged in dairy farming, while 40% were involved in poultry farming. 72 Another study by Kaushik et al, 2021) in Haryana reported that dairy farming was the most popular venture among women agripreneurs, with 68% of them involved in this activity.…”
Section: Economic Characteristic (Activity Wise Distribution)mentioning
confidence: 99%
“…A study by Gupta et al, 2019 found that 60% of women agripreneurs in Rajasthan were engaged in dairy farming, while 40% were involved in poultry farming. 72 Another study by Kaushik et al, 2021) in Haryana reported that dairy farming was the most popular venture among women agripreneurs, with 68% of them involved in this activity.…”
Section: Economic Characteristic (Activity Wise Distribution)mentioning
confidence: 99%